Lean Manufacturing Development Model for Production Cost Reduction in Small and Medium Industries (SMEs) of Tempeh Food with a Green Manufacturing Approach - Purnomo Purnomo; Nanta Sigit; Soetam Rizky Wicaksono; Rudy Setyawan; Novenda Kartika Putrianto; Chandra Wibowo Budiono (Eastasouth Institute, 2026)
The Small and Medium Industry (SMEs) of tempeh food is a strategic sector in supporting food security and local economic empowerment. However, the main challenges faced are high production costs due to waste and low process efficiency. This research aims to develop a Lean Manufacturing model based on the Green Manufacturing approach to reduce production costs in a sustainable manner. The research method involves identifying the type of waste using the Value Stream Mapping (VSM) approach, analyzing the root of the problem with Fishbone diagrams, and designing solutions through the integration of lean and green principles, such as 5S, Kaizen, and environmentally friendly waste management. A case study was conducted on one of the tempeh SMEs in Sanan, Malang City, East Java, Indonesia. The results of the research showed that weekly production costs decreased from IDR 3,188,000 to IDR 2,998,250 (efficiency ±17%), defective products decreased from 4.7% to 1.5% (68% decrease), total processing time decreased from 2,605 minutes to 1,332 minutes (time savings ±14%). Waiting time is reduced by more than 50%. These findings show that the Lean-Green Manufacturing approach not only improves operational efficiency, but also encourages sustainable production practices that are relevant to the development of food SMEs in Indonesia